The contribution of TWIK-1 channels to astrocyte K+ current is limited by retention in intracellular compartments - Wang, Wei; Putra, Adhytia; Schools, Gary P.; Ma, Baofeng; Chen, Haijun; Kaczmarek, Leonard K.; Barhanin, Jacques; Lesage, Florian; Zhou, Min (Frontiers in Cellular Neuroscience, 2013)
TWIK-1 two-pore domain K+ channels are expressed abundantly in astrocytes. In the present study, we examined the extent to which TWIK-1 contributes to the linear current-voltage (I-V) relationship (passive) K+ membrane conductance, a dominant electrophysiological feature of mature hippocampal astrocytes. Astrocytes from TWIK-1 knockout mice have a more negative resting potential than those from wild type animals and a reduction in both inward rectification and Cs+ permeability. Nevertheless, the overall whole-cell passive conductance was not altered significantly in TWIK-1 knockout astrocytes. The expression of Kir4.1 and TREK-1, two other major astrocytic K+ channels, or of other two-pore K+ channels was not altered in TWIK-1 knockout mice, suggesting that the mild effect of TWIK knockout does not result from compensation by these channels. Fractionation experiments showed that TWIK-1 is primarily localized in intracellular cytoplasmic fractions (55%) and mildly hydrophobic internal compartment fraction (41%), with only 5% in fractions containing plasma membranes. Our study revealed that TWIK-1 proteins are mainly located in the intracellular compartments of hippocampal astrocyte under physiological condition, therefore a minimal contribution of TWIK-1 channels to whole-cell currents is likely attributable to a relatively low level presence of channels in the plasma membrane.